2005
DOI: 10.1128/iai.73.4.2281-2287.2005
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin G Isotype Responses to Erythrocyte Surface-Expressed Variant Antigens of Plasmodium falciparum Predict Protection from Malaria in African Children

Abstract: We assessed immunoglobulin G (IgG) isotype responses to variant surface antigens (VSA) expressed on parasite-infected erythrocytes of a panel of heterologous isolates during and after acute episodes in groups of Gabonese children presenting with either mild or severe Plasmodium falciparum malaria. In the acute and convalescent phases IgG3 and IgG1 anti-VSA antibodies, respectively, predominated. In the absence of infection, the levels of both cytophilic isotypes waned, while those of IgG4 increased, particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…Studies have shown that the responses for both non-VSA-PAM 13,14 and VSAPAM [10][11][12][13][14][15] are dominated by the cytophilic subclass IgG1, followed by IgG3 consistent with data obtained from non-pregnant adults and children 14,16,17 . The predominance of IgG1 and IgG3 cytophilic antibody in endemic areas has been associated with either lower parasitaemia 18 or a lower risk of malaria attack 19 .…”
Section: Introductionsupporting
confidence: 62%
“…Studies have shown that the responses for both non-VSA-PAM 13,14 and VSAPAM [10][11][12][13][14][15] are dominated by the cytophilic subclass IgG1, followed by IgG3 consistent with data obtained from non-pregnant adults and children 14,16,17 . The predominance of IgG1 and IgG3 cytophilic antibody in endemic areas has been associated with either lower parasitaemia 18 or a lower risk of malaria attack 19 .…”
Section: Introductionsupporting
confidence: 62%
“…In Kenyan children, antibodies to VSA expressed by autologous parasites were predominantly IgG3 (16). In Gabon, anti-VSA antibodies of the IgG3 subtype were prominent among healthy adults and children (7), and anti-VSA IgG1 and IgG3 were associated with acute malaria infection in children (26).…”
Section: Discussionmentioning
confidence: 99%
“…It is the cytophilic subtypes of antibodies targeting merozoite surface antigens that are associated with clinical and parasitological immunity (for a review, see reference 14), presumably because interaction of anti-merozoite antibodies with Fc receptors plays a critical role. The few studies which have examined the isotype profile of antibodies specific for VSA in nonpregnant individuals suggest that anti-VSA antibodies are also predominantly cytophilic (7,16,18,26).…”
mentioning
confidence: 99%
“…Thus the repeat infection takes place in a different cytokine milieu. This also appears to be the case in humans (30), and may contribute to anti‐disease immunity, because IL‐10 is critical to tip the cytokine balance away from disease (31). Ongoing work will be focused on determining whether there is a malaria‐specific defect in memory cell differentiation or survival in the mouse model.…”
Section: Introductionmentioning
confidence: 97%